Increased TBX6 gene dosages induce congenital cervical vertebral malformations in humans and mice. Issue 6 (30th December 2019) - Ren, Xiaojun; Yang, Nan; Wu, Nan; Xu, Ximing; Chen, Weisheng; Zhang, Ling; Li, Yingping; Du, Ren-Qian; Dong, Shuangshuang; Zhao, Sen; Chen, Shuxia; Jiang, Li-Ping; et al.
Abstract : Background: Congenital vertebral malformations (CVMs) manifest with abnormal vertebral morphology. Genetic factors have been implicated in CVM pathogenesis, but the underlying pathogenic mechanisms remain unclear in most subjects. We previously reported that the human 16p11.2 BP4-BP5 deletion and its associated TBX6 dosage reduction caused CVMs. We aim to investigate the reciprocal 16p11.2 BP4-BP5 duplication and its potential genetic contributions to CVMs. Methods and results: Patients who were found to carry the 16p11.2 BP4-BP5 duplication by chromosomal microarray analysis were retrospectively analysed for their vertebral phenotypes. The spinal assessments in seven duplication carriers showed that four (57%) presented characteristics of CVMs, supporting the contention that increased TBX6 dosage could induce CVMs. For further in vivo functional investigation in a model organism, we conducted genome editing of the upstream regulatory region of mouse Tbx6 using CRISPR-Cas9 and obtained three mouse mutant alleles ( Tbx6 up1 to Tbx6 up3 ) with elevated expression levels of Tbx6 . Luciferase reporter assays showed that the Tbx6 up3 allele presented with the 160% expression level of that observed in the reference (+) allele. Therefore, the homozygous Tbx6 up3/up3 mice could functionally mimic the TBX6 dosage of heterozygous carriers of 16p11.2 BP4-BP5 duplication (approximately 150%, ie, 3/2 gene dosage of the normal level). Remarkably, 60% of the Tbx6 up3/up3 mice manifested with CVMs. Consistent with our observations in humans, the CVMs induced by increased Tbx6 dosage in mice mainly affected the cervical vertebrae. Conclusion: Our findings in humans and mice consistently support that an increased TBX6 dosage contributes to the risk of developing cervical CVMs.